Kontribusi Sektor Non Pertanian Terhadap Pendapatan Rumah Tangga: Studi Kasus di Desa Jirak Kecamatan Sajad Kabupaten Sambas - Fatwa, Muhammad Imam; Sudrajat, Jajat; Oktoriana, Shenny (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The aim of this research is to analyze the structure of household income originating from the non-agricultural and agricultural sectors, as well as analyzing the contribution of non-agricultural sector income to household income. Regarding how big the contribution of non-agricultural income and farming income is to household income. The sample in this research were farmers taken from Jirak Village, namely 42 respondents. The data analysis method used is quantitative with income analysis. The research results show that sources of income from non-agriculture, namely laborers, traders, weaving craftsmen, craftsmen, technicians and furniture, average IDR 1,402,262 per month, while sources of income from rice farming reach an average of IDR 965.972. This shows that non-agricultural income is greater than rice farming income. These results prove that non-agricultural income is seriously used to help with farming and household needs. Then the contribution of non-agricultural income to farmer household income is 59,21 %, this shows that the contribution of non-agricultural income is greater than rice farming income.